Multimodalism and the role of inland waterway system as an infrastructure - 225362 Mohd. Zamani Ahmad; National Seminar on Inland Water Transport (1999 : Kuching, Sarawak) (Skudai : Universiti Teknologi Malaysia, 1999)
08